2009
DOI: 10.1165/rcmb.2007-0364oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Chemokine Receptor CXCR2 in Bleomycin-Induced Pulmonary Inflammation and Fibrosis

Abstract: Pulmonary fibrosis is characterized by chronic inflammation and excessive collagen deposition. Neutrophils are thought to be involved in the pathogenesis of lung fibrosis. We hypothesized that CXCR2-mediated neutrophil recruitment is essential for the cascade of events leading to bleomycin-induced pulmonary fibrosis. CXCL1/KC was detected as early as 6 hours after bleomycin instillation and returned to basal levels after Day 8. Neutrophils were detected in bronchoalveolar lavage and interstitium from 12 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
130
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 50 publications
5
130
0
Order By: Relevance
“…4A ). KC (CXCL1) is a potent chemokine for neutrophils whose receptor was shown to be important for neutrophilic recruitment into the airways of bleomycin-treated mice ( 40 ). While the main source of this increased bronchoalveolar CXCL1 in CD36 Ϫ / Ϫ mice remains to be determined, it is possible that Delayed clearance of neutrophils in zymosan-treated G2A ؊ / ؊ mice Frasch et al reported that antibody-mediated G2A blockade or genetic deletion of G2A both signifi cantly delay the clearance of neutrophils in the murine zymosaninduced peritoneal infl ammation model ( 37,38 ).…”
Section: Discussionmentioning
confidence: 99%
“…4A ). KC (CXCL1) is a potent chemokine for neutrophils whose receptor was shown to be important for neutrophilic recruitment into the airways of bleomycin-treated mice ( 40 ). While the main source of this increased bronchoalveolar CXCL1 in CD36 Ϫ / Ϫ mice remains to be determined, it is possible that Delayed clearance of neutrophils in zymosan-treated G2A ؊ / ؊ mice Frasch et al reported that antibody-mediated G2A blockade or genetic deletion of G2A both signifi cantly delay the clearance of neutrophils in the murine zymosaninduced peritoneal infl ammation model ( 37,38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most notable of these differences were alterations in leukocyte accumulation in the airspaces, although the importance of inflammatory cells in the development of lung fibrosis after injury is a matter of controversy. According to numerous publications, the fibrotic and inflammatory responses to bleomycin appear to be independent of each other (46,(60)(61)(62)(63)(64)(65)(66). Specifically, the systemic depletion of neutrophils or a genetic deficiency in T cells does not prevent the development of fibrosis in the bleomycin model (62,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…The murine CXCR2 (mCXCR2) and its ligands, CXCL1 (keratinocyte-derived chemokine [KC]) and CXCL2/3 (macrophage inflammatory protein 2 [MIP-2]), functional homologues of human growth-related oncogenes (GRO␣, -␤, and -␥), have been identified as the primary chemokine receptor system mediating neutrophil recruitment in various models of acute and chronic inflammation, including Escherichia coli endotoxin-induced acute lung inflammation and injury (6,19,20,23). Both CXCR2 knockout (KO) mice as well as small-molecule inhibitors that interfere with CXCR2 receptor function have shown a role for neutrophils in mediating hyperoxic or ventilator-induced lung injury and in collagen deposition in bleomycin-induced fibrosis (23).…”
mentioning
confidence: 99%
“…Both CXCR2 knockout (KO) mice as well as small-molecule inhibitors that interfere with CXCR2 receptor function have shown a role for neutrophils in mediating hyperoxic or ventilator-induced lung injury and in collagen deposition in bleomycin-induced fibrosis (23). Unlike in influenza virus pneumonia, where CXCR2 is required for neutrophil recruitment but not viral clearance, CXCR2 is important for neutrophil recruitment as well as pathogen elimination in Pseudomonas aeruginosa or Nocardia asteroides pneumonia (18,29).…”
mentioning
confidence: 99%